MicroRNA Expression Analyses in Preoperative Pancreatic Juice Samples of Pancreatic Ductal Adenocarcinoma - Sadakari, Yoshihiko; Ohtsuka, Takao; Ohuchida, Kenoki; Tsutsumi, Kosuke; Takahata, Shunichi; Nakamura, Masafumi; Mizumoto, Kazuhiro; Tanaka, Masao (JOP. Journal of the Pancreas, 2010)
Context Cytological assessment of pancreatic juice is commonly used to diagnose pancreatic ductal adenocarcinoma; however, the sensitivity of cytological assessment has been reported to be low. MicroRNAs are small RNAs regulating various cellular processes and have recently been identified as possible markers of malignant diseases including pancreatic ductal adenocarcinoma. Objective The purposes of this study were to prove the existence of microRNAs in pancreatic juice and to determine whether specific microRNAs in pancreatic juice could be used for detecting pancreatic ductal adenocarcinoma. Methods Relative expression levels of microRNA-21 and microRNA-155 in formalin-fixed paraffin-embedded tissues of resected specimens (no. 13) and pancreatic juice samples collected using preoperative endoscopic retrograde cholangiopancreatography (no. 21) were quantified and their expression levels were then compared to pancreatic ductal adenocarcinoma and chronic pancreatitis. Results Relative expression levels of microRNA-21 in tissue and pancreatic juice samples were significantly higher in pancreatic ductal adenocarcinoma than those in chronic pancreatitis (P=0.009 and P=0.021, respectively). The same results were obtained in the expression levels of microRNA-155 in tissue and pancreatic juice between pancreatic ductal adenocarcinoma and chronic pancreatitis (P=0.014 and P=0.021, respectively). Expression levels of microRNA-21 and microRNA-155 did not correlate with the preoperative cytological results of pancreatic juice. Conclusion MicroRNA-21 and microRNA-155 in pancreatic juice have the potential of becoming biomarkers for diagnosing pancreatic ductal adenocarcinoma. Image: Non-atypical cells in pancreatic juice.